Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1186/s12944-016-0308-2
|View full text |Cite
|
Sign up to set email alerts
|

Lipid composition of circulating multiple-modified low density lipoprotein

Abstract: Atherogenic modified low- density lipoprotein (LDL) induces pronounced accumulation of cholesterol and lipids in the arterial wall, while native LDL seems to lack such capability. Therefore, modified LDL appears to be a major causative agent in the pathogenesis of atherosclerosis. Possible modifications of LDL particles include changes in size and density, desialylation, oxidation and acquisition of negative charge. Total LDL isolated from pooled plasma of patients with coronary atherosclerosis, as well as fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 16 publications
0
37
0
1
Order By: Relevance
“…[12,13,23,32] We have found previously that LDL atherogenicity in CAD patients and diabetic patients correlates negatively with sialic acid levels. [13] Indeed, in vitro studies have shown that desialylated LDL treated with neuraminidase, which removes the sialic acid residues, results in a significant increase in LDL potency to induce lipid accumulation in cultured monocyte-macrophages or intimal cells.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…[12,13,23,32] We have found previously that LDL atherogenicity in CAD patients and diabetic patients correlates negatively with sialic acid levels. [13] Indeed, in vitro studies have shown that desialylated LDL treated with neuraminidase, which removes the sialic acid residues, results in a significant increase in LDL potency to induce lipid accumulation in cultured monocyte-macrophages or intimal cells.…”
Section: Discussionmentioning
confidence: 89%
“…Such separation is possible by using a column with RCA 120 immobilized on CNBractivated agarose. [12,21] Compared with sialylated LDL, desialylated LDL particles are smaller in size and contain more oxysterols, and less phospholipids and antioxidants. [12] In terms of the ability to induce intracellular deposition of lipids, the desialylated LDL fraction is atherogenic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations